Factors affecting mortality in emergency surgery in cases of complicated colorectal cancer - Remzi Kızıltan; Özkan Yılmaz; Abbas Aras; Sebahattin Çelik; Çetin Kotan (Medicinski glasnik, 2016)
Aim: To evaluate retrospectively demographic, clinical and histopathological variables effective on mortality in patients who had undergone emergency surgery due to complicated colorectal cancer. Methods: A total of 39 patients underwent urgent surgical interventions due to complicated colorectal cancer at the Department of General Surgery, Dursun Odabaş Medical Center, between January 2010 and January 2015. Thirty three of these were included in the study. Six patients were excluded because complete medical records had been missing. Medical records of the 33 cases were retrospectively reviewed. Results: There were 14 (42.5%) male and 19 (57.5%) female patients. Mean age was 60 years (range: 32- 83 years); 14 (42.5%) patients were less than 60 years old , while 19 (57.5%) were 60 years old or older. Operations were performed due to perforation (39.3%) and obstruction (60.6%) in 13 and 20 patients, respectively. Tumor localization was in the right and transverse colon in nine (21.2%) and in the left colon in 24 cases (72.7%). Eleven (33.3%) patients underwent resection and anastomosis, 13 (39.3%) resection and ostomy, and nine (27.2%) patients underwent ostomy alone without any resection. Postoperative mortality occurred in nine cases (27.2%). Conclusions: High mortality should be expected in females older than 60 years with a left sided colon tumor or with another synchronous tumor and in perforated tumors. Unnecessary major resections should be avoided and primary pathology should be in the focus of treatment in order to decrease the mortality and morbidity rates.
Keywords: colorectal cancer; perforation; obstruction; mortality